2000
DOI: 10.1002/1097-4660(200006)75:6<491::aid-jctb245>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Separation of the protease enzymes ofBacillus licheniformis from the fermentation medium by crossflow ultrafiltration

Abstract: The separation from fermentation medium of extracellular serine alkaline protease (SAP) enzyme produced by Bacillus licheniformis was investigated using a cross¯ow ultra®ltration system. SAP was separated from the high molecular weight neutral protease (NP) and amylase (AMY) enzymes and from the low molecular weight organic acids and amino acids in a cross¯ow ultra®ltration system with 30 000 Da and 10 000 Da MWCO polysulfone membranes, respectively. The effects of transmembrane pressure (TMP), recirculation v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 19 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Adjalle et al [ 26 ] recorded TMPs of 90 kPa and 100 kPa were optimum values for entomotoxicity recovery from starch industry wastewater and thermal hydrolyzed sludge medium, respectively. Other researcher reported that 20 kPa was best for the separation of serine alkaline protease from neutral protease and amylase and 100 kPa for the separation of serine alkaline protease from the organic and amino acids [ 3 ]. The optimum TMP is different for different cases and may be due to the rheological characteristics and other components present in the feed samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adjalle et al [ 26 ] recorded TMPs of 90 kPa and 100 kPa were optimum values for entomotoxicity recovery from starch industry wastewater and thermal hydrolyzed sludge medium, respectively. Other researcher reported that 20 kPa was best for the separation of serine alkaline protease from neutral protease and amylase and 100 kPa for the separation of serine alkaline protease from the organic and amino acids [ 3 ]. The optimum TMP is different for different cases and may be due to the rheological characteristics and other components present in the feed samples.…”
Section: Resultsmentioning
confidence: 99%
“…The membrane separation processes are the most widespread in the field of biotechnology, and they are more easily operated and scaled up in comparison to other bioseparation processes such as chromatography, and electrophoresis. Among the various membrane separation processes, ultrafiltration is one of the processes that functions under pressure gradient which is mostly used for separation and purification of products including enzymes and other proteins [ 1 3 ] or to recover microbial products (cells and spores) present in a culture medium [ 4 6 ]. Because of the low amount of enzyme present in the cell-free filtrate, the water removal is a primary objective.…”
Section: Introductionmentioning
confidence: 99%
“…embranes 2022, 12, x FOR PEER REVIEW than that obtained in dead-end UF, although the TMP in a cross-flow sys kPa. The performance for dead-end and cross-flow UF of various target solu compared previously [28,29]. In the dead-end mode, the flow is perpen membrane surface, and the solution is pushed under applied pressure.…”
Section: Flux In Cross-flow Uf and Surfactin Recoverymentioning
confidence: 97%
“…The higher TMP results in a faster decrease in fl a pseudo-steady state appears earlier at a lower TMP, which is probably d effect of TMP on the filtration resistance of the membrane surface. The lowest in the case of TMP = 40 kPa; therefore, it was chosen for further exp The performance for dead-end and cross-flow UF of various target solutions has been compared previously [28,29]. In the dead-end mode, the flow is perpendicular to the membrane surface, and the solution is pushed under applied pressure.…”
Section: Flux In Cross-flow Uf and Surfactin Recoverymentioning
confidence: 99%